Walt Disney's Pinocchio - Coco, Eugene Bradley; Dias, Ron; Collodi, Carlo, 1826-1890.; Walt Disney Productions (New York : Golden Book ; Racine, Wis. : Western Pub. Co., 1990)
A wooden puppet full of tricks and mischief, with a talent for getting into and out of trouble, wants more than anything else to become a real boy.
Adaptation of: Avventure di Pinocchio / Carlo Collodi.
Keywords: Fairy tales; Puppets -- Fiction; Fairy tales; Puppets -- Fiction